2021
DOI: 10.1093/ndt/gfab015
|View full text |Cite
|
Sign up to set email alerts
|

A chronic high phosphate intake in mice is detrimental for bone health without major renal alterations

Abstract: Background Phosphate intake has increased in the last decades due to a higher consumption of processed foods. This higher intake is detrimental for patients with chronic kidney disease, increasing mortality and cardiovascular disease risk and accelerating kidney dysfunction. Whether a chronic high phosphate diet is also detrimental for the healthy population is still under debate. Methods We fed healthy mature adult mice over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
(46 reference statements)
2
17
0
Order By: Relevance
“…We employed a graded Pi diet to study the effects of excess Pi on the liver ( Figure 2 ). Studies show conflicting results toward renal and liver health, following supplementation of a high Pi diet ( Baquerizo et al, 2003 ; Haut et al, 1980 ; Ugrica et al, 2021 ). In our study, no significant changes in macroscopic parameters were observed following dietary Pi overload ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…We employed a graded Pi diet to study the effects of excess Pi on the liver ( Figure 2 ). Studies show conflicting results toward renal and liver health, following supplementation of a high Pi diet ( Baquerizo et al, 2003 ; Haut et al, 1980 ; Ugrica et al, 2021 ). In our study, no significant changes in macroscopic parameters were observed following dietary Pi overload ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ingestion of these food types, where significant amounts of highly bioavailable phosphate-based preservatives are added to improve taste and increase shelf life, has led to an ongoing debate as to whether these preservatives impact human health outcomes [ 10 , 11 ]. While evidence for phosphate toxicity in humans might not be conclusive, a high dietary phosphate burden has been reported to induce significant changes in vascular calcification [ 8 ] and bone health in rodent models [ 12 ]. Recent rodent studies have also provided unexpected insights into the short- and long-term hormonal adaptions that occur in response to dietary phosphate load [ 12 ], which may change our understanding and perception of human disease outcomes.…”
Section: Phosphate Homeostasis In Health and Diseasementioning
confidence: 99%
“…While evidence for phosphate toxicity in humans might not be conclusive, a high dietary phosphate burden has been reported to induce significant changes in vascular calcification [ 8 ] and bone health in rodent models [ 12 ]. Recent rodent studies have also provided unexpected insights into the short- and long-term hormonal adaptions that occur in response to dietary phosphate load [ 12 ], which may change our understanding and perception of human disease outcomes.…”
Section: Phosphate Homeostasis In Health and Diseasementioning
confidence: 99%
“…Fast food and soda also contain high levels of phosphate additives [ 9 , 11 ]. A high-phosphate diet (HPD) detrimentally affects bone health [ 12 ], is a risk factor in cardiorenal syndrome [ 13 ], and is correlated with a higher all-cause mortality [ 14 ]. However, the effects of HPD on metabolic function, and specifically on white adipose tissue, remain largely understudied [ 15 ].…”
Section: Introductionmentioning
confidence: 99%